To Develop Treatment of Acute Phase Diabetic Osteoarthropathy in Diabetic Foot Syndrome - Ismailov U.S; Matmuratov K.J; Yakhubov I.Y (Zien Journals, 2023)
In this article, we can get an effective result by using timely adequate treatment of diabetic osteoarthropathy in patients with diabetic paw syndrome who have diabetic osteoarthropathy. In doing so, we can prevent this disease from recurring and possible further complications by applying the necessary treatment in a case that takes into account each phase of diabetic osteoarthropathy.
Keywords: diabetic osteoarthropathy; diabetic foot; diabetes mellitus.